Improving the students’ writing proficiency through collaborative writing Method - Ismail, Ismail; Ramadhan, Ramadhan (Maspul Journal of English Studies, 2019)
Purposes: The objective of the research was intended to know the improvement of the students’ proficiency in writing through collaborative writing method at second year students’ of SMA Muhammadiyah Kalosi, Enrekang regency. Methodology: The method of this research is classroom action research consisted of two cycles. The population of this research is all students grade eight at Senior high school; they were 350 students and as a sample of this research consist of ten percent from the population. There were two kinds of data on this research namely qualitative and quantitative. Qualitative data showed that students’ interest in writing descriptive because they can write collaboratively, knowledge sharing and critical thinking in teaching and learning process. Quantitative data showed us the improvement from the first up to the last test, the improvement occurred continuously. Findings: The finding of the research was students’ improvement in cycle I of content was17.25% became 19.37%. The students’ improvement of organization was 19.71% in cycle 1 and it became 20.42% in cycle 2. The students’ improvement of vocabulary was 13.54% in cycle 1 and it became 14.09% in cycle 2. The students’ improvement of language use was 14.71% in cycle 1 and it became 16.63% in cycle 2, and the students’ improvement of mechanics was 3.42% in cycle 1 and it became 3.72% in cycle 2. Implication: It describes us that there was an improvement on students’ proficiency by implementing collaborative writing method.